USING KEYWORD MNEMONICS STRATEGY TO IMPROVE STUDENTSâ€™ VOCABULARY ACHIEVEMENT OF PHYSICAL EDUCATION AND RECREATION DEPARTMENT, FACULTY OF PHYSICAL EDUCATION AND HEALTH OF PGRI UNIVERSITY OF BANYUWANGI - Untari, Dewi (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2015)
Abstract This study is aimed at improving the vocabulary achievement of the students using â€œKeyword Mnemonic Strategyâ€. This strategy is selected because it is an effective and helpful for the students in learning English vocabulary. The research problem is how can Keyword Mnemonics strategy improve studentsâ€™ vocabulary achievement at Physical Education and Recreation Department of PGRI University of Banyuwangi. This study employs classroom action research design in which the researcher acts as the lecturer who conducts the teaching activity while her collaborator is positioned as the observer who observes the lecturerâ€™s performance and the studentsâ€™ activities during the teaching learning process. The subject of this study is the students of Physical Education and Recreation Department, Faculty of Physical Education and Health of PGRI University of Banyuwangi. The cycle of the research consist of four major steps: planning of action, implementation of action, analysis, observation and reflection. The instruments used to collect data are test, observation checklist and questionnaire. The study is completed in cycle two. The finding of the research in cycle 1 shows that the studentsâ€™ vocabulary score has improve. But, the score do not achieved the criteria of success. In cycle 2, the studentsâ€™ score achieve the criteria of success. Based on the findings, it can be known that the improvement of the studentsâ€™ average score has improved from 64.66 in cycle 1 to 79.66 in cycle 2. It can be concluded that teaching vocabulary using â€œKeyword Mnemonic Strategyâ€ can improved the studentsâ€™ vocabulary score. In this strategy, the students learn the five steps of keyword mnemonic strategy. They are: (1) Make a keyword (2) Think the picture (3) Produce the definition (4) Find the synonym and (5) Make a sentence. By using those five steps, the students can easily memorize the meaning of the target words. Cycle two shows that by creating their own keywords, students easiest to memorize the meaning of the words and they have long-term memory. Besides that, by creating their own keyword mnemonic, the students become a creative students. They free to create their own keyword to make their learning more enjoyful and more easy to understand. Key words: Keyword Mnemonic, Improving, Vocabulary